Navigating Digital Transformation and Cultural Resistance at PT. Nusantara Textile Manufacturing (MTN) - M, Raipandi; Musana, Ali; Febriyati, Wahyuni; Anugerah Sucipto, Bernadiktio; Akhmad Ramdan, Aboneo; Permata Sari, Della Ayu (Hut Publication Business and Management, 2025)
This study analyzes the failure of digital transformation at PT. Manufaktur Tekstil Nusantara (MTN), triggered by the misalignment between radical innovation and a traditional bureaucratic culture. Using a qualitative library research method, the study employs the Burke-Litwin Model for causal diagnosis, the McKinsey 7S Framework for internal assessment, and the Stakeholder Matrix to map resistance. The results indicate that the failure resulted from prioritizing “Hard” elements (technology) over “Soft” elements (staff and shared values), leading to severe economic insecurity and resistance among senior employees. The analysis confirms that the lack of a proper “Unfreezing” phase and poor change leadership caused the stagnation. Consequently, the study proposes a recovery strategy based on Kotter’s 8-Step Model, emphasizing the need to re-establish urgency and build a guiding coalition to align digital competence with organizational culture.